2009
DOI: 10.1128/jcm.01070-09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Aspergillus Species Collected for the Transplant-Associated Infection Surveillance Network

Abstract: A large aggregate collection of clinical isolates of aspergilli (n ‫؍‬ 218) from transplant patients with proven or probable invasive aspergillosis was available from the Transplant-Associated Infection Surveillance Network, a 6-year prospective surveillance study. To determine the Aspergillus species distribution in this collection, isolates were subjected to comparative sequence analyses by use of the internal transcribed spacer and ␤-tubulin regions. Aspergillus fumigatus was the predominant species recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
211
6
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(245 citation statements)
references
References 18 publications
10
211
6
18
Order By: Relevance
“…In recent years, sequence-based molecular methods have been used successfully for species identification in this group, particularly methods using the calmodulin gene, which can distinguish all species within section Nigri (4-6). Molecular studies indicated that several species in addition to A. niger were able to cause human infections; different regions had different species of pathogenic black Aspergillus, and A. niger and Aspergillus tubingensis were the most frequently identified pathogens in previous studies (2,(7)(8)(9)(10)(11)(12)(13)(14). Additionally, it is worth noting in a clinical context that azoles exhibited different activity against the two species and that isolates from different geographical regions exhibited remarkable differences in susceptibility to azoles and amphotericin B (1-13, 15).…”
Section: Molecular Identification and In Vitro Antifungal Susceptibilmentioning
confidence: 99%
“…In recent years, sequence-based molecular methods have been used successfully for species identification in this group, particularly methods using the calmodulin gene, which can distinguish all species within section Nigri (4-6). Molecular studies indicated that several species in addition to A. niger were able to cause human infections; different regions had different species of pathogenic black Aspergillus, and A. niger and Aspergillus tubingensis were the most frequently identified pathogens in previous studies (2,(7)(8)(9)(10)(11)(12)(13)(14). Additionally, it is worth noting in a clinical context that azoles exhibited different activity against the two species and that isolates from different geographical regions exhibited remarkable differences in susceptibility to azoles and amphotericin B (1-13, 15).…”
Section: Molecular Identification and In Vitro Antifungal Susceptibilmentioning
confidence: 99%
“…According to the order of frequency, A. fumigatus, A. flavus, and A. niger were recently isolated as agents of invasive aspergillosis in our hospital (11). Isolations of A. lentulus defined in 2005 as a kind of new Aspergillus species were reported in America, Japan, South Korea, Australia, and Spain (9,12). The characteristics of some cases with colonisation or infection caused by A. lentulus in the literature are shown in Table 1 (3,8,9,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…CDC also performed confirmatory testing on fungal specimens from other laboratories, including a fungal isolate recovered by FDA from a BBG vial and fungal DNA isolated by an outside laboratory from a vitreous cassette specimen. Fungal isolates were identified by morphologic and DNA sequence analysis (15). Fusarium isolates were compared by multilocus sequence analysis (16); species of Bipolaris isolates were identified by examination of the ribosomal internal transcribed spacer region (15).…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Fungal isolates were identified by morphologic and DNA sequence analysis (15). Fusarium isolates were compared by multilocus sequence analysis (16); species of Bipolaris isolates were identified by examination of the ribosomal internal transcribed spacer region (15).…”
Section: Laboratory Testingmentioning
confidence: 99%